2004
DOI: 10.4028/www.scientific.net/jmnm.20-21.151
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ni-Al and Ni-Al-X Phases by Mechanical Alloying

Abstract: The Ni-Al phases were synthesized in the composition range 40-85 at. % Ni by mechanical alloying (MA) of elemental component mixtures. MA of Ni-Al powders produces the B2 phase in the range 40 -61 at. % Ni and a solid solution Ni(Al) -in the range 65-85 at. % Ni. Milling of Ni 62.5 Al 37.5 composition results in formation of the B2 and Ni(Al) phases mixture. Formation of a supersaturated solid solution for 65-75 at. % Ni were accompanied by appearance of B2 phase at the intermediate MA stage. Ball milling of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…For compositions of Ni-25 at.%Al some authors [3,4] reported the formation of Ni(Al) supersaturated solid solution by mechanical alloying, however Pabi et al [5] reported the presence of disordered Ni 3 Al for this composition. Other authors have work on phase transformations of the intermetallic NiAl when adding a third element during milling [9][10][11]. Consolidation of the milled powders by hot pressing and by extrusion has also been carried out [12][13][14][15], the authors obtained high strength at room and elevated temperatures and good compressive ductility.…”
Section: Introductionmentioning
confidence: 95%
“…For compositions of Ni-25 at.%Al some authors [3,4] reported the formation of Ni(Al) supersaturated solid solution by mechanical alloying, however Pabi et al [5] reported the presence of disordered Ni 3 Al for this composition. Other authors have work on phase transformations of the intermetallic NiAl when adding a third element during milling [9][10][11]. Consolidation of the milled powders by hot pressing and by extrusion has also been carried out [12][13][14][15], the authors obtained high strength at room and elevated temperatures and good compressive ductility.…”
Section: Introductionmentioning
confidence: 95%